2019
DOI: 10.1021/jacs.9b01829
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Understanding of the Free Energy Landscape in Early Stages of Metal–Organic Framework Nucleation

Abstract: The assembly mechanism of hierarchical materials controlled by the choice of solvent and presence of spectator ions. In this paper, we use enhanced sampling molecular dynamics methods to investigate these effects on the configurational landscape of metal-linker interactions in the early stages of synthesis, using MIL-101(Cr) as a prototypical example. Microsecond-long welltempered metadynamics (WTmetaD) simulations uncover a complex free energy structural landscape, with distinct crystal (C) and non-crystal (N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…[18,19] In particular, the rich conformational ensemble unveiled during the association of SBUs, highlights the importance of entropic contributions in defining the free energy landscape of MIL-101(Cr) precursors. [18] Moreover, the propensity of healing defects in the crystal lattice, as well as the formation of crystal-like SBUs is impacted by solution composition. The relative abundance of different isomers of half-SBUs precursors, as well as the presence of spectator ions emerge as key variables in this context.…”
Section: Doi: 101002/adts202000092mentioning
confidence: 99%
See 2 more Smart Citations
“…[18,19] In particular, the rich conformational ensemble unveiled during the association of SBUs, highlights the importance of entropic contributions in defining the free energy landscape of MIL-101(Cr) precursors. [18] Moreover, the propensity of healing defects in the crystal lattice, as well as the formation of crystal-like SBUs is impacted by solution composition. The relative abundance of different isomers of half-SBUs precursors, as well as the presence of spectator ions emerge as key variables in this context.…”
Section: Doi: 101002/adts202000092mentioning
confidence: 99%
“…[18] Furthermore, the AA SBU is the largest source of crystal-like growth units building the MIL-101(Cr) lattice. [18] This analysis allows for an evaluation of the conformational freedom that different intermediates experience in solution. This, in turn, provides a detailed description of their accessible structural fluctuations, and provides further insight into the nature of the ensemble of configurations sampled by precursors during self-assembly and nucleation.…”
Section: Doi: 101002/adts202000092mentioning
confidence: 99%
See 1 more Smart Citation
“…They also found free energy barriers that are associated with structural rearrangements and solvent interactions that are disrupted in an amorphous-to-crystalline transition. Similarly, Kollias and co-workers[371] calculate free energies to explore the role that solvent and counterions play in the early-stage nucleation of MIL-101. They found that the stability of the early structures and the presence of amorphous vs. crystalline moieties can be affected by the identity of the solvent and ions present in solution.…”
Section: Orienting the Fieldmentioning
confidence: 99%
“…Metadynamics (MTD) is an enhanced sampling method that increases the probability of reaching high free-energy states by adding a Gaussian bias potential to the Hamiltonian of a state 6,7 . The MTD method has been used to analyze reaction pathways [8][9][10][11][12][13][14][15] , the conformations of additives at crystal surfaces [16][17][18][19] , crystal structures [20][21][22][23][24][25] , crystal nucleation [26][27][28][29][30][31][32][33] , drug design [34][35][36][37][38] , and the transport mechanism of an ion in a sub-nanopore 39 . The MTD method affords a free-energy landscape in a space of collective variables (CVs) for a system of interest.…”
mentioning
confidence: 99%